1980
DOI: 10.1017/s0014479700010796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield Stability in Intercropping: Studies on Sorghum/Pigeonpea

Abstract: S U M M A R Y Data from 94 experiments on sorghum/pigeonpea intercropping were examined for evidence that the stability of yield is greater with intercropping than sole cropping. Stability of the major component (sorghum) was examined by calculating the distribution of yields; stability of the overall intercropping system was examined by calculating coefficients of variation, by computing regressions of yield against an environmental index, and by estimating the probability of monetary returns falling below gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(111 citation statements)
references
References 5 publications
6
105
0
Order By: Relevance
“…The highest grain yield of maize from 50% population of soybean variety Boshe might be due to reduction in competition for growth resources due to its early maturity of the intercropped variety. This result was in conformity with that of Rao (1980) who reported that early maturing legume varieties could lead to increased productivity of the cereal component. The yield reduction due to 75% population of variety Ethio Yugoslavia might be due to its late maturity (141.55 days) which was almost same with the maize component.…”
Section: Maize Component Yield and Yield Componentssupporting
confidence: 92%
“…The highest grain yield of maize from 50% population of soybean variety Boshe might be due to reduction in competition for growth resources due to its early maturity of the intercropped variety. This result was in conformity with that of Rao (1980) who reported that early maturing legume varieties could lead to increased productivity of the cereal component. The yield reduction due to 75% population of variety Ethio Yugoslavia might be due to its late maturity (141.55 days) which was almost same with the maize component.…”
Section: Maize Component Yield and Yield Componentssupporting
confidence: 92%
“…It increases total production in addition to stabilization of production in the rainfed areas (Rao and Willey, 1980). Intercropping provides an opportunity to avoid crop competition and advantages of increased production (Rahman, 1999 andMondal et al, 1999) and greater profit margin (Evans, 1960;Grimes, 1963) and gives higher resource use efficiency (Hashem and Moniruzzaman, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases intercropping improves the reliability of the legume component in particular. In the system studied by Rao and Willey (1980), i.e. sorghum/pigeonpea cultivation in India, it was estimated that monocrops would fail once in five to eight years, but intercrops in only one year out of 36.…”
Section: Introductionmentioning
confidence: 99%